A case of nonalcoholic Wernicke's encephalopathy due to an extreme diet based on magnetic resonance imaging features (Medical Journal of Indonesia, 2019)
Wernicke's encephalopathy is a rare occurrence in Indonesia because alcohol consumption is very low. However, in Indonesia, Wernicke's encephalopathy could be triggered by an inadequate intake of thiamine (vitamin B1) due to an extreme diet for several months. It is a case of a 31-year-old male, who presented to the emergency room with a decreased level of consciousness. According to the family, for the last few weeks, he has become less responsive and less attentive. Fluid-attenuated inversion recovery (FLAIR) magnetic resonance imaging (MRI) revealed a unique picture with symmetrical lesions in the bilateral medial thalamus, mammillary bodies, periaqueductal gray matter, and the dorsal surface of the medulla oblongata. Clinically, there is no neck stiffness and no fever. The laboratory results from the blood and cerebrospinal fluid have ruled out meningitis. Treatment with thiamine 200 mg t.i.d. has shown an excellent response and significant clinical improvement. The earlier thiamine substitution treatment is started, the better the outcome because thiamine will prevent further injury to the brain and enhance recovery.